The Phenomenon of Comparing the Fundamentalist Lesson to the Jurisprudential Lesson: Monitoring and Criticism - Al-Fouzan, Mohammed Tariq Ali (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: The research aims to elucidate the comparative aspects between the foundational lesson (Usul al-Fiqh) and the jurisprudential lesson (Fiqh). This is achieved by examining this phenomenon, highlighting its priorities and conditions, and conducting analysis and criticism to gain insight into its variations. Methods: The study employed a method of observation through comprehensive retrospective examination of the history and works of the field, utilizing both analytical and critical methodologies. Results: The research concluded that Al-Shirazi was among the pioneers who aimed to condense Usul al-Fiqh due to his jurisprudential interest. This trend flourished with Ibn al-Hajib, followed by the idea of abstracting foundational texts from evidence, as proposed by Al-Qaṭī’i and Ibn al-Sabki. Finally, the principle of summarization led to the emergence of works combining both foundational and jurisprudential aspects, such as those by Ibn al-Mubarrad and Ibn al-Najjar al-Fatḥi. All of these represent facets of comparing foundational lessons with jurisprudence. Conclusion: The study revealed that the aspects of comparing foundational lessons with jurisprudence manifest in conceiving Usul al-Fiqh as denominational, akin to the denominationality of Fiqh. There is also the notion of categorizing concise summaries based on the balance of jurisprudential lessons. Additionally, there is a tendency to adhere to jurisprudential lessons in abstracting foundational lessons from evidence and opinions, without considering the inherent differences in the nature of the two disciplines, which should account for the necessity of variations in teaching methods.